CHANGES IN SALIVA SECRETION IN THE CONTEXT OF TEETH LOSS - Dana Gabriela Budală; Carina Balcoș; Florinel Cosmin Bida; Dragoș Ioan Virvescu; Elena Raluca Baciu; Zinovia Surlari (Romanian Society of Oral Rehabilitation, 2021)
In the field of medical research there is a current trend to explore the importance and symptoms of saliva. This question, which more and more researchers in the forensic, systemic and dental fields have tried to answer and at the same time bring arguments for paying more attention, is related to the exhaustive and diagnostic role of saliva in the patient's health. Conclusions. Given the central role that saliva plays in maintaining oral health and the benefits of using saliva as a diagnostic tool, a general knowledge of the basic physiology of saliva is important from the point of view of clinical practice.